PLSSSSSSS HELPPPPPPP I WILL GIVE BRAINLIESTTTTTTTTTT!!!!!!!!!!!!!!!!!!!!!PLSSSSSSS HELPPPPPPP I WILL GIVE BRAINLIESTTTTTTTTTT!!!!!!!!!!!!!!!!!!!!!PLSSSSSSS HELPPPPPPP I WILL GIVE BRAINLIESTTTTTTTTTT!!!!!!!!!!!!!!!!!!!!!PLSSSSSSS HELPPPPPPP I WILL GIVE BRAINLIESTTTTTTTTTT!!!!!!!!!!!!!!!!!!!!!PLSSSSSSS HELPPPPPPP I WILL GIVE BRAINLIESTTTTTTTTTT!!!!!!!!!!!!!!!!!!!!!PLSSSSSSS HELPPPPPPP I WILL GIVE BRAINLIESTTTTTTTTTT!!!!!!!!!!!!!!!!!!!!!

PLSSSSSSS HELPPPPPPP I WILL GIVE BRAINLIESTTTTTTTTTTPLSSSSSSS HELPPPPPPP I WILL GIVE BRAINLIESTTTTTTTTTTPLSSSSSSS HELPPPPPPP I WILL GIVE BRAINLIESTTTTTTTTTTPLSS class=

Respuesta :

Answer: X=4 Y=-6

Step-by-step explanation:

Well we know that y= -4x+10

So we can input that into the bottom equation

2x +2(-4x+10) = -4

2x +-8x+20=-4

-6x + 20= -4

-6x = -24

x = 4

We also have to find the value of Y

y=-4(4)+10

y= -16 + 10

y=-6

DWRead

Answer:

Step-by-step explanation:

2x + 2y = -4

Substitute (-4x+10) for y:

2x + 2(-4x+10) = -4

2x -8x + 20 = -4

-6x = -24

x = 4